Interplay between Heightened Temporal Variability of Spontaneous Brain Activity and Task-Evoked Hyperactivation in the Blind - Dai, Rui; Huang, Zirui; Tu, Huihui; Wang, Luoyu; Tanabe, Sean; Weng, Xuchu; He, Sheng; Li, Dongfeng (Frontiers in Human Neuroscience, 2016)
The brain's functional organization can be altered by visual deprivation. This is observed by comparing blind and sighted people's activation response to tactile discrimination tasks, like braille reading. Where, the blind have higher activation than the sighted upon tactile discrimination tasks, especially high activation difference is seen in ventral occipitotemporal (vOT) cortex. However, it remains unknown, whether this vOT hyperactivation is related to alteration of spontaneous activity. To address this question, we examined 16 blind subjects, 19 low-vision individuals and 21 normally sighted controls using functional magnetic resonance imaging (fMRI). Subjects were scanned in resting-state and discrimination tactile task. In spontaneous activity, when compared to sighted subjects, we found both blind and low vision subjects had increased local signal synchronization and increased temporal variability. During tactile tasks, compared to sighted subjects, blind and low-vision subject's vOT had stronger tactile task-induced activation. Furthermore, through inter-subject partial correlation analysis, we found that temporal variability is more related to tactile-task activation, than local signal synchronization's relation to tactile-induced activation. Our results further support that vision impairment induces vOT cortical reorganization. The hyperactivation in the vOT during tactile stimulus processing in the blind may be related to their greater dynamic range of spontaneous activity.